Aprendizaje basado en problemas como estrategia metodológica para el desarrollo del pensamiento crítico en la asignatura de Física. - Labanda Ordoñez, Leonardo Mauricio (2023)
The objective of this research is to analyze how the methodological strategy of problem-based learning (PBL) contributes to the development of critical thinking in second year students of the General Unified Baccalaureate (BGU) in unit 1 of Physics. It was developed with a methodology based on a qualitative approach, the method used was the documentary review, the information was synthesized through the checking, the elaboration of search logbooks and library index cards. From the results obtained, the existing relationship between the conceptual categories stands out, highlighting the complementary contribution of PBL in the development of critical thinking, which takes an innovative dynamic that responds positively to the identified need. Even so, it is necessary to emphasize that for Physics learning, PBL does adapt to its needs because it allows in its development to contextualize knowledge through problem solving. Key words: Active methodology; higher order thinking; critical thinking, teaching and learning.